Food Preferences and Price, but Not Value, Were Associated with Sales in a Discounted Food-Buying Program. Issue 3 (4th May 2021) - Galie, Krista A.; Hanson, Karla L.
ABSTRACT: Discounted food-buying (DFB) programs aim to enhance food security among low-income households through sales of aggregated food packages at low cost. This study used the theory of planned behavior to investigate content, price, and value in relationship to the decision to purchase DFB packages. Mixed methods included a cross-sectional survey of low-income consumers (n = 76), and an analysis of 3 years of program sales data. Respondents reported protein, vegetables, and fruit of highest importance, and were willing to pay more for protein packages. Sales were associated with price, but not measured value after controlling for seasonality. Unwanted items were the leading barrier to purchase. DFB programs that prioritize food preferences and price may enhance sales to low-income consumers.